Effects of valence and causal direction in the emotion inferences processing during reading: Evidence from a lexical decision task - León, Jose A.; Dávalos, María T.; Escudero, Inmaculada; Olmos, Ricardo; Morera, Yurena; Froufe, Manuel (Anales de Psicología / Annals of Psychology, 2015)
In two experiments we investigated the role that activation of emotional inferences when readers represent fictional characters' emotional states using an affective lexical decision task. Subjects read short stories that described concrete actions. In the first experiment, we analyzed whether the valence (positive or negative) was an important factor of inference´s activation. The results showed that valence was determinant factor in the moment that emotional inference was generated, being the positive valence faster than negative. In the second experiment we studied whether the emotion inference activation was influenced by the causal direction of the story, where the causal direction of the text was manipulated in order to induce towards an emotional inference predictive (the reader looking for a consequence that promote a particular emotion) or inducing an explanatory inference (reader looking for a cause that “explain” a particular emotion). The results suggest that emotional inferences are made online, and that valence and causal directions are two decisive components of emotional trait, but only positive valence increase their processing.